Irrigation depth and biochar doses on the vegetative growth of cherry tomato - G. T. M. Kubo; H. O. C. Guerra; L. H. G. Chaves; J. D. Fernandes; A. A. R. da Silva; J. N. F. de Andrade; L. G. S. Laurentino; A. J. T. Mendonça; T. F. L. Arruda; M. S. F. Araújo (Brazilian Journal of Biology)
Abstract Cherry tomato (Solanum lycopersicum var. cerasiforme) cultivation has become a very profitable option due to its high added value. Therefore, using technologies for water control and soil conditioners is a possible way to increase profitability for producers. Thus, the objective of the present study was to assess the effects of irrigation and poultry litter biochar on the vegetative growth of cherry tomato, ‘Carolina’ cultivar. The experiment was conducted in a semi-protected greenhouse of UAEA/UFCG campus in Campina Grande, PB, Brazil, using a completely randomized design, in a 4 x 4 factorial scheme with 3 replicates and in split plots. The factors studied were four levels of irrigation (70, 80, 90 and 100% of soil field capacity) and four doses of poultry litter biochar (0, 4, 8 and 12 t.ha-1). In the evaluation of plant height in relation to irrigation depth, a percentage increase of 33.19% was observed between the highest and lowest irrigation depths (70% and 100% of field capacity) at the end of the experiment. Regarding stem diameter in relation to irrigation depth variation, there was an increase of 5.5 mm from 47 to 107 days after germination. Poultry litter biochar influenced stem diameter, resulting in a percentage gain of 6.91% between the lowest and highest doses (0 and 12 t.ha-1). For leaf area, there was a percentage increase of 18.1% when comparing the lowest and highest irrigation depths (70% and 100% of field capacity).